2014
DOI: 10.12816/0023975
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Insufficiency : Prevalence and Effect of Compression Stockings

Abstract: Introduction: Chronic venous insufficiency (CVI) is a common disease affecting mainly lower limbs and significantly influencing the quality of life. This study aims to estimate the prevalence of CVI in the Qassim Region and test the effectiveness of compression stockings as an intervention option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…This data is not entirely consistent with other reports which suggest a significantly higher incidence of CVD. A study completed in 2014 in Saudi Arabia suggests that the incidence of CVD is at the level of 61.6% (women: 69%, men: 45%) [4]. A study by Vuylstke et al, based on the assessment of CVD symptoms by 406 GPs in Belgium and Luxembourg (a total of 6009 study patients reporting to GPs), suggests the occurrence of CVD symptoms, especially the feeling of heaviness, pain and oedema in 61.3% of respondents [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is not entirely consistent with other reports which suggest a significantly higher incidence of CVD. A study completed in 2014 in Saudi Arabia suggests that the incidence of CVD is at the level of 61.6% (women: 69%, men: 45%) [4]. A study by Vuylstke et al, based on the assessment of CVD symptoms by 406 GPs in Belgium and Luxembourg (a total of 6009 study patients reporting to GPs), suggests the occurrence of CVD symptoms, especially the feeling of heaviness, pain and oedema in 61.3% of respondents [5].…”
Section: Discussionmentioning
confidence: 99%
“…Tomasz Urbanek, Andrzej Dorobisz, Marcin Gabriel, Włodzimierz Hendiger, Arkadiusz Jawień, Marcin Kucharzewski, Grzegorz Madycki, Zbigniew Rybak, Walerian Staszkiewicz, Tomasz Zubilewicz, Krzysztof Ziaja introduction Chronic venous diseases (CVD) of the lower limbs belong to the most common diseases of the vascular system. Epidemiological studies related to CVD suggest that they affects 2-56% of men and 1-73% of women; the incidence in the population significantly increases with age [1][2][3][4]. Significant differences related to the extremely diverse reported incidence of CVD result from the differences between study populations and from the evaluation methods adopted by authors of these publications [1,[5][6][7].…”
mentioning
confidence: 99%
“…The use of class 1 (10–15 mmHg) CS for four weeks significantly increased QoL compared with and placebo pressure (3–6 mmHg) stockings 27 ) . In a similar study, it was observed that a four-week use of CS increases QoL and improves symptoms of CVI 28 ) .…”
Section: Discussionmentioning
confidence: 83%
“…Two studies [9,10] support the use of compression stockings in the treatment of chronic venous disease in patients under 70 years old, whereas the effectiveness is not known in older populations. Systematic reviews about post-thrombotic syndrome [11][12][13][14] and pain [11] in patients with deep venous thrombosis show uncertain effects.…”
Section: Introductionmentioning
confidence: 99%